Peningkatan Kualitas Pendidikan Islam Melalui Metode Pembelajaran Perspektif Al-Qur'an dan Hadits - Setyoningsih, Kattrin; Zahrah, Vira Aisah; Syafira, Intan Nur; Thobroni, Ahmad Yusam (Journal of Islamic Education, 2024)
The aim of this research is to describe the various learning methods contained in the Al-Qur'an and Hadith as a form of contribution to the world of education. Qualitative research methodology by reviewing various related literature as well as analyzing several scientific works that explain learning methods from the perspective of the Koran and Hadith. The research results show that the Al-Qur'an and Hadith as a guide to life for mankind provide varied learning methods. Several learning methods, namely the imitation method, the practical experience method (Trial and Error Method), and the thinking method. In conclusion, learning involves thinking activities (brain training) and behavioral activities (behavior) which must influence the growth of knowledge and experience. Islam highly upholds the aspect of morality in education because it holds that all knowledge essentially belongs to Allah and learning should be done not solely for the sake of knowledge itself, but also to get closer to Allah, worship Him, and fulfill obligations as caliph- His in the world